Innovativeness of Enterprises in Poland in the Regional Context - Anna Golejewska (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The artcle examines the innovatveness of enterprises in 69 Polish NUTS3 sub-regions in 2014. The analysis is based on unpublished regional data from the Polish Central Statstcal Ofce covering the following variables: the share of enterprises which have incurred outlays for innovatve actvites, the share of enterprises implementng process or product innovatons, the share of companies collaboratng in the feld of innovaton, and the share of new or modernized products in total producton sold in industrial companies. The analysis focuses on building rankings and cluster analysis of NUTS3 regions. As research methods, the author uses selected methods of multdimensional comparatve analysis, principal component analysis and the hierarchical Ward’s method. The results show that there are substantal diﬀerences among NUTS3 sub-regions as regards innovatveness of enterprises. The low level of cooperaton does not foster innovaton. Innovaton outputs of enterprises are also unsatsfactory. The highest variaton is seen in the share of new or modernized products in total producton sold in industrial companies. The fnal eﬀect of the cluster analysis is the division of regions into 7 groups. In the case of units where innovaton inputs are not reﬂected in innovaton outputs, it would be useful to explore regional and local factors inﬂuencing those relatons. Further research is stll needed.